Efficacy of combination therapy of amphotericin and posaconazole in treatment of mucormycosis - Sridhara S; Ramesh Sanappa; Nandini P; Gayatri Jayan; Gangadhara KS (Creative Pharma Assent, 2023)
Background: Mucormycosis is an opportunistic systemic fungal infection which is debilitating caused by order Mucorales. The standard management of mucormycosis consists of aggressive debridement of the infected tissue and parenteral anti-fungal therapy with Amphotericin B. Liposomal amphotericin B is a “true” liposomal formulation of amphotericin B with greatly reduced nephrotoxicity and minimal infusion-related toxicity. Very minimal data is available on the usefulness of combining different antifungal agents for an effective outcome. Our study was undertaken at a time when there was a huge turnover of mucormycosis cases during Covid 19 pandemic with resultant shortage of important resources including liposomal amphotericin B. In effect, combination of liposomal amphotericin B with posaconzole gave a promising outcome. Objectives: To study the efficacy of combination therapy of liposomal amphotericin B and posaconazole in the treatment of mucormycosis. Methodology: It is a prospective study of 43 patients with mucormycosis who received combination therapy based on their disease severity. Results: In our study, 16 (37%) were considered as patients with mild disease, 18 (41.8%) were considered as patients with moderate disease and 9 patients (20.9%) were considered as severe. 20 (58%) patients out of 34 patients with mild to moderate disease showed improvement after combination therapy. Conclusion: A significant percentage of patients in our study showed improvement with combination therapy of liposomal amphotericin B and posaconazole in terms of survival and disease recurrence.